A DNA-based approach to infer species diversity of larvae and adults from the white grub genus Phyllophaga (Coleoptera: Scarabeidae) - Guzmán-Franco, Ariel W.; Rivero-Borja, Maribel; Marín-Jarillo, Antonio; Tamayo-Mejía, Fernando; Guzmán-Santillán, Nayra; Guzmán-Santillán, Tania (Frontiers in Insect Science, 2024)
Scarabaeoidea is a diverse and widely distributed insect group; many are agricultural pests including species within the genus Phyllophaga. Species diversity studies in this taxonomic group are done mainly using morphological identification; however, despite existing taxonomic keys for adults and larvae, identification can be difficult due to their complex morphology. Molecular taxonomy can increase the value and accuracy of morphological species identification of larvae and adults. To test this, larvae collected from soil close to maize plants were identified using molecular taxonomy methods, and compared with adults captured using light traps. The larvae (2021) and adults (2022) were sampled on maize at the same locations in central Mexico. The molecular identification of larvae and adults were performed using three regions within the Cytochrome oxidase gene (cox), two in the Cytochrome c oxidase subunit 1 (cox1), Cytochrome b (CytB) and 28S rDNA. Cox gene information was more useful than nuclear information (28S). The combined morphological and molecular taxonomy used on adults distinguished between seven Phyllophaga species.Although two closely related species, P. polyphyla and P. ravida, were distinguished using cox gene information, a greater resolution was obtained using CytB. All analyses identified cryptic species within P. vetula. Species found amongst sampled adults were similar to those found amongst larvae. However, the number of species was greater in adults than in larvae at some locations. Larval information showed Phyllophaga community structure changed over time. Our findings will contribute to a better understanding of Phyllophaga's ecology in maize.